If mayors ruled the world : dysfunctional nations, rising cities - Barber, Benjamin R., 1939-2017 (Yale University Press, 2013)
"In the face of the most perilous challenges of our time--climate change, terrorism, poverty, and trafficking of drugs, guns, and people--the nations of the world seem paralyzed. The problems are too big for governments to deal with. Benjamin Barber contends that cities, and the mayors who run them, can do and are doing a better job than nations. He cites the unique qualities cities worldwide share: pragmatism, civic trust, participation, indifference to borders and sovereignty, and a democratic penchant for networking, creativity, innovation, and cooperation. He demonstrates how city mayors, singly and jointly, are responding to transnational problems more effectively than nation-states mired in ideological infighting and sovereign rivalries. The book features profiles of a dozen mayors around the world, making a persuasive case that the city is democracy's best hope in a globalizing world, and that great mayors are already proving that this is so"--